NEPA, a fixed oral combination of netupitant and palonosetron, improves control of chemotherapy-induced nausea and vomiting (CINV) over multiple cycles of chemotherapy: results of a randomized, double-blind, phase 3 trial versus oral palonosetron - Aapro, Matti; Karthaus, Meinolf; Schwartzberg, Lee; Bondarenko, Igor; Sarosiek, Tomasz; Oprean, Cristina; Cardona Huerta, Servando; Hansen, Vincent; Rossi, Giorgia; Rizzi, Giada; Borroni, Maria Elisa; Rugo, Hope (2017)
Abstract Purpose Antiemetic guidelines recommend co-administration of targeted prophylacticmedicationsinhibitingmolecular pathwaysinvolvedinemesis.NEPAisafixedoralcombinationofa newNK1receptorantagonist(RA),netupitant(NETU300mg), and palonosetron (PALO 0.50 mg), a pharmacologically distinct 5-HT3 RA. NEPA showed superior prevention of chemotherapy-inducednauseaandvomiting(CINV)compared with oral PALO in a single chemotherapy cycle; maintenance of efficacy/safetyover continuingcycles is the objectiveof this study. Methods This study is a multinational, double-blind study comparing a single oral dose of NEPA vs oral PALO in chemotherapy-naïve patients receiving anthracycline/ cyclophosphamide-based chemotherapy along with dexamethasone 12 mg (NEPA) or 20 mg (PALO) on day 1. The primary efficacy endpoint was delayed (25–120 h) complete response (CR: no emesis, no rescue medication) in cycle 1. Sustained efficacy was evaluated during the multicycle extension by calculating the proportion of patients with overall (0–120 h) CR in cycles 2 –4 and by assessing the probability of sustained CR over multiple cycles. Results Of 1455 patients randomized, 1286 (88 %) participated in the multiple-cycle extension for a total of 5969 cycles; 76 % completed ≥4 cycles. The proportion of patients with an overall CR was significantly greater for NEPA than oral PALO for cycles 1–4 (74.3 vs 66.6 %, 80.3 vs 66.7 %, 83.8 vs 70.3 %, and 83.8 vs 74.6 %, respectively; p ≤ 0.001 each cycle). The cumulative percentage of patients with a sustained CR over all 4 cycles was also greater for NEPA (p < 0.0001). NEPA was well tolerated over cycles. Conclusions NEPA, a convenient, guideline-consistent, fixed antiemetic combination is effective and safe over multiple cycles of chemotherapy. Keywords Neurokinin-1receptorantagonist .NEPA . Netupitant .Palonosetron .CINV.Multiplecycles